Synthesis of C1 inhibitor in fibroblasts from patients with type I and type II hereditary angioneurotic edema. - Kramer, J (1991)
Patients with hereditary angioneurotic edema (HANE) have serum levels of functionally active inhibitor of the first component of complement (C1 INH) between 5 and 30% of normal, instead of the 50% expected from the single normal allele. Increases in rates of catabolism have been documented in patients with HANE and certainly account for some of decrease in C1 INH level. A possible role for a decrease in synthesis of C1 INH in producing serum levels of C1 INH below the expected 50% of normal has not been well studied. We studied the synthesis of C1 INH in skin fibroblast lines, which produce easily detectable amounts of C1 INH. In type I HANE cells, C1 INH synthesis was 19.6 +/- 4.0% (mean +/- SD) of normal, much less than the 50% predicted. In type II HANE cells, the total amount of C1 INH synthesis (functional and dysfunctional) was 98.9 +/- 17% of normal; the functional protein comprised 43% of the total. Thus, type II HANE cells synthesized functional C1 INH at a much greater rate than for the type I cells. In both type I and II HANE cells, amounts of steady-state C1 INH mRNA levels paralleled rates of C1 INH synthesis, indicating that control of C1 INH synthesis occurred at pretranslational levels. Both type I and type II fibroblasts synthesized normal amounts of C1r and C1s. These data suggest that the lower than expected amounts of functionally active C1 INH in type I HANE may be due, in part, to a decrease in rate of synthesis of the protein, and that the expressions of the normal C1 INH allele in HANE is influenced by the type of abnormal allele present.